Respostas fisiológicas do maracujazeiro (Passiflora edulis SIMS) ao alagamento - Rossi, Magda dos Santos (2011)
Espírito Santo state has edaphoclimatic conditions propitious to the cultivation of passion fruit tree, however, the average rainfall does not pose constant, resulting in extended periods of drought and periods of torrential rain. Therefore, assessing the physiological responses of plants of passion fruit tree (Passiflora edulis Sims) FB 200 and FB 300 cultivars submitted to water stress by flooding is the main way to identify and characterize the effects of duration of stress and select genetic material with a high degree of tolerance. Passion fruit tree plants were grown in a greenhouse and kept in well-drained soil until the start of treatment. Ultimately we used FB 200 and FB 300 cultivars employing three experimental treatments: 1. Unflooded plants, 2. Plants flooded for 3 days, 3. Plants flooded for seven days. In all treatments the plants had a recovery period (with soil drainage) of seven days. The flooding caused a decrease in water potential, stomatal conductance, and CO2 liquid assimilation rate on both cultivars during the flooding. Yet the reason between the internal and environmental concentration of CO2 (Ci/Ca) increased from the fifth day of flooding in both cultivars due to increased internal carbon. The phases O-J and J-I of the OJIP curve, presented greater changes during the flooding indicating the reduction of the PSII acceptor side (QA and QB) and the progressive reduction of the plastoquinone pool, respectively. The stress by flooding also resulted in the decrease of connectivity of units of PSII (with L-band positive) and inactivation of oxygen evolution complex (K-Band). The catalase and peroxidase activity increased significantly in cultivar FB 200 during the stress. After seven days of recovery the cultivars recovered the photosynthetic activity when submitted to short periods of flooding (three days). However, when the period of flooding was prolonged (seven days) the stress became more severe to a point of not having recovery of the photosynthetic activity